1993
DOI: 10.1172/jci116662
|View full text |Cite
|
Sign up to set email alerts
|

Small elevations of glucose concentration redirect and amplify the synthesis of guanosine 5'-triphosphate in rat islets.

Abstract: Recent studies suggest a permissive requirement for guanosine 5'-triphosphate (GTP) in insulin release, based on the use of GTP synthesis inhibitors (such as mycophenolic acid) acting at inosine monophosphate (IMP) dehydrogenase; herein, we examine the glucose dependency of GTP synthesis. Mycophenolic acid inhibited insulin secretion equally well after islet culture at 7.8 or 11.1 mM glucose (51% inhibition) but its effect was dramatically attenuated when provided at < 6.4 mM glucose (13% inhibition; P < 0.001… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
1

Year Published

1994
1994
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 49 publications
(37 reference statements)
0
50
0
1
Order By: Relevance
“…200 islets per condition were cultured overnight ( 18-20 h) in RPMI-1640 medium (containing 10% FBS, 100 U/ml penicillin, 100 g/rm1 of streptomycin, 5 mM Hepes, 2 Ci/ml [3H]hypoxanthine and 11.1 mM glucose) and MPA when indicated. We have previously shown that [3H] hypoxanthine can be used to label both adenine and guanine nucleotides through the salvage pathway of purine nucleotide synthesis (8). After the culture period, islets were washed five times with 1 ml ice-cold KRB (pH 7.4, gassed with 95%02/5% CO2, and containing 16.7 mM glucose and 0.2% BSA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…200 islets per condition were cultured overnight ( 18-20 h) in RPMI-1640 medium (containing 10% FBS, 100 U/ml penicillin, 100 g/rm1 of streptomycin, 5 mM Hepes, 2 Ci/ml [3H]hypoxanthine and 11.1 mM glucose) and MPA when indicated. We have previously shown that [3H] hypoxanthine can be used to label both adenine and guanine nucleotides through the salvage pathway of purine nucleotide synthesis (8). After the culture period, islets were washed five times with 1 ml ice-cold KRB (pH 7.4, gassed with 95%02/5% CO2, and containing 16.7 mM glucose and 0.2% BSA).…”
Section: Methodsmentioning
confidence: 99%
“…The NTP/NDP ratios reported in the Results section are from the TLC method unless otherwise stated. In addition, eluant trinucleotide HPLC fractions were collected every 18 s and were matched against the concomitant UV chromatograms as previously described (8) for calculation of specific activities. Samples were counted for 5 min in 4 ml of scintillation cocktail.…”
Section: Methodsmentioning
confidence: 99%
“…Under these conditions, MPA reduces GTP levels by Ͼ 80% (and GTP/ GDP ratio by Ͼ 60%) in isolated islets; coprovision of guanine or guanosine completely reverses the reduction in GTP (or GTP/GDP ratio) elicited by MPA (2,3). After this, islets were washed twice with Krebs-Ringer medium consisting of BSA (0.1%) and glucose (11.1 mM) and were labeled with [ 3 H]methionine (50 Ci/ml; 1 ml total volume) for 2 h at 37 Њ C. The labeling was terminated by addition of ice-cold Krebs-Ringer medium.…”
Section: Protein Prenyl-cysteine Carboxyl Methylation Assaymentioning
confidence: 99%
“…Recently, using specific inhibitors of guanosine triphosphate (GTP) synthesis, we identified a permissive role for GTP as one of the modulators of physiologic insulin secretion (2,3). However, the exact sites of action of GTP in pancreatic ␤ cells have not been identified thus far.…”
Section: Introductionmentioning
confidence: 99%
“…For example, using selective inhibitors of GTP biosynthetic pathway [e.g., mycophenolic acid], a permissive role for GTP in GSIS was first established in [10][11][12]. Although the exact molecular and cellular mechanisms underlying the regulatory role[s] of GTP remain only partially understood, available evidence indicates that it might involve activation of one [or more] G-proteins.…”
Section: 1: Evidence For a Requisite Role For The Methylation Of Thmentioning
confidence: 99%